Indigenous music and academic achievement in elementary social studies - Navales, Jeanie N. Moral (2006)
Singing and music have always played important roles in the transmittal of culture especially among Filipinos. This study investigated the effects of integrating indigenous music in Heograpiya, Kasaysayan, at Sibika (HKS) lessons particularly those about the different regions of the Philippines. Two Grade IV classes in Camalig North Central School in Albay were selected as experimental and control groups. Indigenous music was integrated in HKS lessons in the experimental group while the control group used traditional teaching methods. It was concluded that indigenous music integration has positive effects on pupil achievement in HKS 4 and also enhances the teaching of the subject. Major learning domains such as Social Studies and music are compatible in imparting specific knowledge to students.